GLMM (Gaussian distribution) (species random effect) results evaluating the difference between air and thorax temperature (Tth-Tair – variable response) with thorax width of Anisoptera and Zygoptera (predictor). - Lenize Batista Calvão (7530623) (2025)
GLMM (Gaussian distribution) (species random effect) results evaluating the difference between air and thorax temperature (Tth-Tair – variable response) with thorax width of Anisoptera and Zygoptera (predictor).